Análisis Documental de la prevalencia de Mycobacterium bovis mediante prueba de tuberculina - Cumbicos Jiménez, Josselyn Esthefania (2021)
Bovine Tuberculosis is an infectious-contagious disease of great zoonotic potential, whose causative agent is Mycobacterium bovis, a member of the complex agent Mycobacterium tuberculosis, which causes tuberculosis in humans. This agent affects cattle, being typical of this species, however, it can manifest itself in wild, domestic animals and in humans, causing respiratory and enteric conditions; It should be noted that this pathology in its initial stage usually shows asymptomatically, and manifests itself when there is depression of the immune system or in its old age, generating losses in milk and meat production and negatively influencing public health. Bovine tuberculosis can be transmitted through direct contact between animals, or contact with secretions or gums expelled by infected animals; in the case of humans, its transmission can occur through the intake of unpasteurized dairy products and consumption of raw meats. The tuberculin intradermal test is the most used method for the diagnosis of this pathology, assessing delayed hypersensitivity reactions, rapid methods of nucleic acid detection by PCR can also be performed. The incidence at the national level through studies carried out in the coastal region indicate that there are 7.57% of cases diagnosed by tuberculin test, according to several authors this is related to race, type of production and sex.